2015
DOI: 10.1515/sdj-2015-0018
|View full text |Cite
|
Sign up to set email alerts
|

Dental Anxiety: Etiology and Treatment Options

Abstract: Summary Dental anxiety might be the cause of serious health problems. Avoiding dental visits can lead to complications with functional, esthetic and sociological consequences. In order to have a simple and efficient dental procedure, it is very important to diagnose dental anxiety and to react adequately. The aim of this paper is using available literature to present most frequent causes, consequences as well as treatment options for dental anxiety. Treating dental anxiety and choosing the right treatment is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…Dental anxiety is oftentimes correlated with anxiety, pain, and fear, and the prevalence of anxiety in these patients varies worldwide. In North America, the population with dental anxiety ranges from 10% to 20%, while it is 11% in Germany and 10% in Norway [1]. Soares et al reported that 46% of 100 Brazilian children aged 5-8 years had dental anxiety [2].…”
Section: Dental Anxietymentioning
confidence: 99%
See 3 more Smart Citations
“…Dental anxiety is oftentimes correlated with anxiety, pain, and fear, and the prevalence of anxiety in these patients varies worldwide. In North America, the population with dental anxiety ranges from 10% to 20%, while it is 11% in Germany and 10% in Norway [1]. Soares et al reported that 46% of 100 Brazilian children aged 5-8 years had dental anxiety [2].…”
Section: Dental Anxietymentioning
confidence: 99%
“…A fear of the dentist consists of dental anxiety, dental fear, and dental phobia; dental anxiety is generally benign, whereas dental phobia is the most intensive type. There are strong correlations between dental anxiety and poor oral health, an increased level of caries, and behavioral management problems in children, because an anxious patient tends to resist dental treatment, and this usually leads to irregular dental visits [1].…”
Section: Dental Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…This fear is one of the main reasons for oral health care neglect. Under the concept "fear of dentist, " it is possible to distinguish dental anxiety, dental fear and dental phobia [1].…”
Section: Introductionmentioning
confidence: 99%